Desertification and Climate Change in Africa - African Group of Negotiators Expert Support (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Desertification has increased in African drylands in recent decades, led by land use change, climatic variability and poor land management practices. People living in drylands in Africa are highly vulnerable to desertification and climate change, because of their impacts on a wide range of livelihood based resources. Desertification and climate change affect gender disproportionately, with women and youth being the most affected. Without implementation of adequate measures, climate change will exacerbate the vulnerability to desertification among dryland populations in Africa. Policy responses and integrated land management practices, as well as indigenous and local knowledge are needed to consider the complex and multi-faceted nature of causes and effects of desertification.